Refugee Worlding: M.I.A. and the Jumping of Global Borders. Issue 1 (2nd January 2021) - Bui, Long T.
ABSTRACT: This article analyzes the life and work of refugee-turned-singer M.I.A. to explain the concept of refugee worlding, the transversal intersectional modes of being a refugee. Exploring the artist's unique aesthetics as well as her play with time-space, I indicate the ways such a practice is emblematic of the creative and critical methodology of Critical Refugee Studies (CRS). As a border hopper, M.I.A.'s imaginative mobilization and weaponizing of refugee-ness jump scales, musical and otherwise, a disruption of the militarized contexts that drive the flight of migrants. Such artprop takes stock of the many world(s) forged, embodied, performed, and crafted on refugee-centered terms.